Engine valve seat wear study on compressed natural gas (CNG)by using nano powder - Ramasamy, D. (2013)
In automotive engineering, the research of alternative fuel is crucial to reduce dependency to the cost increasing for the use of gasoline. There is also need to find the best configuration of engine to match the alternative fuel. One of the current fuels capable to compete with gasoline in our country is Compressed Natural gas (CNG). This fuel is readily available in refilling stations nationwide and is used by Natural Gas Vehicle (NGV) on the road. Most of the engines use this fuel by retro-fitting existing engines with little or no modification to the existing gasoline engine. Hence, the performance of the engine using CNG is compromised. The purpose of the project is to find the mechanism that causes valve seat wear on CNG bi-fuel engines. A combination of CFD simulation for boundary input of experiment and experimental work will be used to determine valve wear rate. A fabrication of the stand alone valve tester enables precise work of measuring forces on a valve seat. A microscope picture will show the effect of valve wear rate. The significance of the project is to increase durability of bi-fuel CNG driven engines.